The Importance of Shifting Disturbance Regimes in Monarch Butterfly Decline and Recovery - Haan, Nathan L.; Landis, Douglas A. (Frontiers in Ecology and Evolution, 2019)
The Eastern migratory monarch butterfly has declined in recent decades, partly because widespread adoption of herbicide-resistant corn and soybean has nearly eliminated common milkweed from crop fields in the US Midwest. We argue that in addition to milkweed loss, monarch declines were likely exacerbated by shifting disturbance regimes within their summer breeding range. Monarchs prefer to lay eggs on younger, vegetative milkweed stems. They also benefit from enemy-free space, as most eggs and early-instar larvae succumb to predators. Historically, ecological disturbances during the growing season could have provided these conditions. During most of the 19th and 20th centuries, milkweed was abundant in crop fields where manual weeding and mechanical cultivation set milkweed back, but rather than killing it would often stimulate regrowth later in the summer. Before European settlement, large mammals and fires (natural and anthropogenic) perturbed grasslands during the summer and could have had similar effects. However, presently most remaining milkweed stems in the Midwest are in perennial grasslands like roadsides, old-fields, parks, and conservation reserves, which often lack growing season disturbance. As a result, monarchs may be left with limited options for oviposition as the summer progresses and could have lower survival in grasslands where predation pressure is high. Our recent work has shown that targeted disturbance during the growing season produces milkweed stems that are attractive to ovipositing monarchs and harbor fewer arthropod predators. Targeted disturbance in perennial grasslands could improve habitat heterogeneity and phenologic diversity of milkweeds, and should be explored as a monarch conservation strategy.